The Dynamical Processes of Biodiversity Case Studies of Evolution and Spatial Distribution - Grillo, Oscar; Venora, Gianfranco (IntechOpen, 2011)
Driven by the increasing necessity to define the biological diversity frame of widespread, endemic and threatened species, as well as by the stimulating chance to describe new species, the study of the evolutive and spatial dynamics is in constant execution. Systematic overviews, biogeographic and phylogenic backgrounds, species composition and distribution in restricted areas are focal topics of the 15 interesting independent chapters collected in this book, chosen to offer to the reader an overall view of the present condition in which our planet is.